The Google Form and Microsoft Excel applications: Non-Cognitive Initial Diagnostic Test Instrument for Guidance and Counseling Teachers - Imam Tabroni; Tyas Novi Andhika; M. Irfanul Firdaus; M. Arif Iskandar (International Journal of Educatio Elementaria and Psychologia, 2024)
This research is motivated by the lack of effectiveness and efficiency of the implementation of the distribution of non-cognitive initial diagnostic tests conducted by Guidance and Counseling teachers. The very long time allocation makes many Guidance and Counseling teachers unwilling to carry out the initial non-cognitive diagnostic test because it requires up time for other student assistance services. The Non-Cognitive Initial Diagnostic Test is very important to do as student learning profiling, which can be used as initial data in conducting differentiated learning. This study aims to determine the effectiveness and efficiency of the use of Google Forms and Ms Excel applications as non-cognitive initial diagnostic test instruments for Guidance and Counseling teachers. The type of research is descriptive qualitative. Data collection uses observation, interviews and documentation studies. Data validity techniques using triangulation techniques. The results of research use the Five Stages method, namely the Preliminary Research Stage, Model Development Stage, Model Validation Stage, Effectiveness Test Stage, and Dissemination Stage. Google Forms and Ms. Excel have ease of operation, distribution, data processing and accessibility. Google Forms and Ms. Excel a very appropriate combinations of applications for conducting non-cognitive diagnostic tests, because of their effectiveness efficiency and operation.